Measuring the vulnerability of subnational regions - Wim Naudé; Mark McGillivray; Stephanié Rossouw (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2008)
A small but growing literature has been concerned about the economic (and environmental) vulnerability on the level of countries. Less attention is paid to the economic vulnerability of different regions within countries. By focusing on the vulnerability of subnational regions, our paper contributes to the small literature on the vulnerability of place. We see the vulnerability of place as being due to vulnerability in various domains, such as economic vulnerability, vulnerability of environment, and governance, demographic and health fragilities. We use a subnational dataset on 354 magisterial districts from South Africa, recognize the potential relevance of measuring vulnerability on a subnational level, and construct a local vulnerability index (LVI) for the various districts. We condition this index on district per capita income and term this a vulnerability intervention index (VII) interpreting this as an indicator of where higher income per capita, often seen in the literature as a measure of resilience, will in itself be unlikely to reduce vulnerability.
Keywords: O18; O55; R58; 330; vulnerability; regional development; decentralization; South Africa; Regionale Entwicklung; Dezentralisierung; Südafrika